Magnetic field simulation of pinch mode magnetorheological fluid valve - Mohd Zul Asri, Mohd Ramli (2016)
This thesis presents the magnetic field simulation of magnetorheological fluid using finite element method. Magnetorheological fluid (MRF) is a smart material fluid carrying small magnetic particles. There are four operational mode of MRF that is squeeze mode, valve mode, shear mode and pinch mode. This thesis will focus on pinch mode which is named as magnetic gradient pinch mode (MGP). The objective of this thesis is to develop a design concept of a magnetic gradient pinch mode valve. It is very important to develop a concept design because it can help in finding the possible design configuration in producing a magnetic gradient pinch shape inside the valve from the reaction of the electromagnetic. From the concept design, simulation was conducted using Finite Element Method Magnetics (FEMM) software to get the magnetic flux density, B and magnetic field intensity, H produced by MGP valve. By getting the magnetic flux density from the finite element analysis, magnetic saturation was prevented in the valve. Magnetic saturation happened when the magnetic flux density at the valve gap is more than the maximum magnetic flux density of the MRF at 0.78 T. Magnetic field intensity, H, determine the generated maximum yield stress. One of the proposed design which is the third design, was exhibit highest magnetic flux density, B than other two design. Therefore, the thrird design is suitable for MGP valve due to abality to produce highest yield stress, thus, can withstand higher pressure when applied.